BENTUK-BENTUK INSTRUMEN DALAM MENILAI PENGUASAAN MUFRODAT - Selma Meila Puspita; Syihabuddin Syihabuddin (Postgraduate of IAIN Metro Lampung Indonesia, 2020)
Arabic is the second language studied by many madrasas and pesantren in Indonesia. It is important to continue to improve the quality of Arabic language learning by evaluating all learning activities. One of them is evaluation of assessment instruments. The research instrument is a tool used to obtain data about the process and learning outcomes of students which are carried out systematically and continuously so that it becomes meaningful information in decision making. In education, there are many forms of assessment instruments that can be used to measure and assess the learning process and outcomes that have been carried out. Mufrodate learning as the object of study in this study also uses various forms of assessment instruments. In the seventh grade Arabic book published by the Ministry of Religion in 2014, we can find the forms of assessment instruments for mufradât mastery. One of them is a similar instrument that has been developed in a study such as a picture instrument (card). Other forms such as description instruments, multiple choice, wording, matchmaking and so on are popular instruments that are also used in this book.